1993
DOI: 10.1080/09553009314551081
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Chromosome Painting as a Biodosimeter in Human Peripheral Lymphocytes Following Acute Exposure to Ionizing Radiationin Vitro

Abstract: Fluorescence in situ hybridization with chromosome-specific composite DNA probes ('chromosome painting') appears to be a useful tool for quantifying symmetrical cytogenetic damage. However, a thorough comparison between chromosome painting and the conventional methods of GTG-banding and dicentric analysis has not been performed. We have undertaken the validation of chromosome painting using human blood exposed in vitro to 137Cs gamma-rays at doses ranging from 0 to 400 cGy, then cultured according to standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(55 citation statements)
references
References 20 publications
0
54
0
1
Order By: Relevance
“…However, the actual observed rates of radiation-induced translocations are higher in general than that of dicentrics (1.63-9 fold, Lucas et al 1989;1-12.33 fold, Cremer el al. 1990; 1.5-2 fold, Natarajan et al 1992; 1-3 fold, Tucker et al 1993;1.67-4 fold, Boei et al 1996; greater than 1, VirsikPeuckert et al 1997;1.4 fold, Finnon et al 1995;1.3-3.75 fold, Luomahaara et al 1999;1.55-2.79 fold, Schmid et al 1992;1.11-3.67 fold, Bauchinger et al 1993; an observed high number in translocations at most dose points, Nakano et al 1993;1.2 fold, Knehr et al 1999). A study previously reported from our laboratory (Kanda et al 1996), in which cells in the second division and misclassification of aberrations were carefully excluded, also showed a slightly higher number of translocations, although the difference was not statistically significant.…”
Section: Introductionmentioning
confidence: 99%
“…However, the actual observed rates of radiation-induced translocations are higher in general than that of dicentrics (1.63-9 fold, Lucas et al 1989;1-12.33 fold, Cremer el al. 1990; 1.5-2 fold, Natarajan et al 1992; 1-3 fold, Tucker et al 1993;1.67-4 fold, Boei et al 1996; greater than 1, VirsikPeuckert et al 1997;1.4 fold, Finnon et al 1995;1.3-3.75 fold, Luomahaara et al 1999;1.55-2.79 fold, Schmid et al 1992;1.11-3.67 fold, Bauchinger et al 1993; an observed high number in translocations at most dose points, Nakano et al 1993;1.2 fold, Knehr et al 1999). A study previously reported from our laboratory (Kanda et al 1996), in which cells in the second division and misclassification of aberrations were carefully excluded, also showed a slightly higher number of translocations, although the difference was not statistically significant.…”
Section: Introductionmentioning
confidence: 99%
“…In an in vitro study using ionizing radiation exposure with 137Cs gamma rays, Tucker et al (9) compared translocation detection between G-banded chromosomes and painting of chromosome 4 and chromosomes 1, …”
Section: Resultsmentioning
confidence: 99%
“…For example, chromosome aberrations are the standard biodosimeter for radiation exposure (Tucker et al, 1993;Bauchinger, 1998;Finnon et al, 1999). This role reflects the relative ease of detecting aberrations and well-defined dose-response relationships.…”
Section: Radiation-induced Genomic Instability and Cancermentioning
confidence: 99%